Chronic co-exposure to low levels of brominated flame retardants and heavy metals induces reproductive toxicity in zebrafish. (September 2018) - Chen, Jiangfei; Ma, Xue; Tian, Linjie; Kong, Aijun; Wang, Nengzhuang; Huang, Changjiang; Yang, Dongren
Brominated flame retardants (BFRs) and heavy metals (HMs) are two main types of pollutants in electronic waste recycling sites, which are also ubiquitously detectable in environmental media and human tissues. However, the adverse health effects of exposure to the mixture of these types of pollutants are unknown. In this study, we investigated the reproductive toxicity of a mixture of decabromodiphenyl ether (BDE-209), tetrabromobisphenol A, cadmium chloride, and lead acetate (PbAc) at the environmental relevant levels. Zebrafish were waterborne and exposed to chemical mixtures for one generation. The reproductive effects were evaluated for F0 adults and F1 offspring. Chemical residues were also analyzed in the exposed adults and their eggs at the end of exposure. Our findings demonstrated that exposure to the chemical mixture for 150 days had no effect on the survival rate of zebrafish, but it decreased body length and weight in females and increased body weight and condition factor in males. The mixture exposure resulted in a female-biased sex ratio in adults and decreased sperm density and motility in males and egg production in females. For the F1 offspring, decreased fertilization, delayed hatching, and increased malformation were found in all exposure groups. In conclusion, chronic co-exposure to BFRs and HMs at the environmental relevant levels not only affected growth, sex ratio, and sperm quantity/quality and egg production in adults but also reduced the reproductive success in the offspring, implying that multi-pollutants in the environmental media may pose a public health risk to other exposed organisms or human beings.